Determination of the effects of cryoablation for atrial fibrillation on esophageal functions - Muhammet Buğra Karaaslan; Ali Deniz; Ismail Cem Eray; Sedef Kuran; Sevinc Puren Yucel; Ozsun Serkan Sonmez; Aziz Inan Çelik; Onur Sinan Deveci; Mesut Demir; Mehmet Kanadası; Ayhan Usal (Anatolian Journal of Cardiology)
Objective: Periesophageal vagal plexus injury is a complication of cryoablation for atrial fibrillation (AF). The aim of this study is to investigate the effect of cryoablation on esophageal functions and to determine the relationship between esophageal temperature and esophageal motility. Methods: Twenty patients with symptomatic paroxysmal AF who underwent cryoablation were included in this study. The lowest cryoballoon temperature for each pulmonary vein (PV) was recorded. Esophageal temperature was measured using an esophageal probe during each cryoapplication. Esophageal manometry was performed before the procedure and one day after the procedure for each patient in order to assess the esophageal functions. Results: During the procedure, the highest esophageal temperature change was found in the left-side PVs in 13 patients (65%) and in the right-side PVs in seven patients (35%). No correlation was found between the lowest cryoballoon temperature and esophageal temperature change (r=0.22, p=0.05). It was detected that the lower esophageal sphincter pressure and esophageal contraction amplitude pressure decreased after the procedure (before: 19.7+-9.3 mm Hg, after: 14.3+-4.9 mm Hg, p=0.001; before: 84.5+-28.3 mm Hg, after: 72.7+-34.3 mm Hg, p=0.005, respectively). Five patients (25%) developed gastrointestinal symptoms after the procedure. Conclusion: During cryoablation, esophageal temperature measurement can be performed to reduce the probability of esophageal injury. Cryoablation affects esophageal motility, and esophageal manometry can be performed to detect esophageal motility impairments in patients with gastrointestinal symptoms.